Refinement and enhancement of high-Nb TiAl alloy via in-situ precipitation of Ti2AlC and TiB2 nanoparticles - Yingchao Guo; Yongfeng Liang; Dingbang Sun; Huijun Wang; Junpin Lin (Journal of Materials Research and Technology, 2024)
An in-situ dual morphology of Ti2AlC/TiB2 nanoparticles was refined and enhanced to fabricate Ti-47.7Al-7.1Nb-2.3V-1.1Cr composites via induction hot-pressing sintering with nano-B4C addition. The generation process of nanoparticles, lamellar refinement mechanism, and effect of nanoparticles on the microstructure evolution/mechanical properties were meticulously analysed. With 0.2 at% nano-B4C addition, Ti2AlC/TiB2 nanoparticles were uniformly distributed in the matrix following sintering. In addition, upon sintering at 1425 °C for 10 min under a pressure of 50 MPa, the lamellar colony size decreased from 280 ± 145 μm to 55 ± 16 μm, and the ultimate tensile strength (UTS) increased by 116 MPa, 142 MPa, and 176 MPa, when tested at room temperature, 800 °C, and 900 °C, respectively. The enhanced mechanical properties were attributed to the synergistic effects of grain refinement strengthening, solid solution strengthening, the Orowan mechanism, and twinning strengthening.